2020
DOI: 10.3390/microorganisms8060930
|View full text |Cite
|
Sign up to set email alerts
|

Removal Ability and Resistance to Cinnamic and Vanillic Acids by Fungi

Abstract: Twelve fungal strains were assayed to investigate their resistance to cinnamic and vanillic acids and their ability to remove these compounds from a liquid medium. In a first step, the effect of the two aromatic acids (1 g/L) on the fungal growth kinetic was studied. The results were modelled through a logistic like function (Dantigny equation) to estimate τ, which is the time to the half-maximum colony diameter. The key findings of this part were as follows: (i) generally, cinnamic acid exerted a stronger eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Hesperidin is a strong antifungal and is active against A. parasiticus , A. flavus , F. semitectum and P. expansum [ 47 ]. Vanillic acid exhibits antimicrobial activity against Enterobacter cloacae and E. hormaechei strains; further, it induces a delay in the development of Trichoderma spp., Athelia rolfsii , Phaeoacremonium parasiticum , A. niger and F. oxysporum [ 48 , 49 , 50 ]. The R. officinalis extract also contains other derivatives of caffeic acid, that could act as ligands for metal ions; thus, they react with peroxide radicals and stabilize free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Hesperidin is a strong antifungal and is active against A. parasiticus , A. flavus , F. semitectum and P. expansum [ 47 ]. Vanillic acid exhibits antimicrobial activity against Enterobacter cloacae and E. hormaechei strains; further, it induces a delay in the development of Trichoderma spp., Athelia rolfsii , Phaeoacremonium parasiticum , A. niger and F. oxysporum [ 48 , 49 , 50 ]. The R. officinalis extract also contains other derivatives of caffeic acid, that could act as ligands for metal ions; thus, they react with peroxide radicals and stabilize free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…The antifungal action of vanillic acid on L. theobromae , C. gloeosporioides , F. oxysporum , P. parasiticum , P. italicum , A. niger , A. alternate , and Trichoderma sp. recorded lower effects compared to ferulic acid and p-coumaric acid [ 144 ]. Regarding the antibacterial activity, vanillic acid influences both human bacterial pathogens and those from agriculture or food.…”
Section: Common Applications—perspectivesmentioning
confidence: 99%
“…[7][8][9] Cinnamic acid is an aromatic carboxylic acid that occurs naturally in diverse plants, including vegetables, Cinnamomum cassia, fruits and other substances. 10 Many studies have found that cinnamic acid derivatives have promising biological activities, including antibacterial, [11][12][13] antifungal, [14][15][16] antiviral, 17 anti-inflammatory, 18 anticancer 19 and insecticidal, 20 as well as prominent herbicidal activity, 21,22 which has led to cinnamic acid attracting widespread attention from pharmaceutical chemists (Figure 1). Meanwhile, caffeic acid (3, 4-dihydroxy cinnamic acid) and ferulic acid (3-methoxy-4-hydroxycinnamic acid), as classic analogs of cinnamic acid, also possess an excellent antiviral profile in the fields of medicine and pesticides.…”
Section: Introductionmentioning
confidence: 99%